Exploring the Relational Embeddedness of Higher Educational Students During Hungarian Emergency Remote Teaching - Győri, Krisztina; Pusztai, Gabriella (Frontiers in Education, 2022)
In 2020, the researchers started studying with utmost haste the effect of the COVID-19 pandemic on teaching. The name of the form of teaching that came to be is disputed, neither the phrase of distance teaching nor digital teaching are professional enough. We use the term of emergency remote teaching (henceforth ERT), which appears in the scientific literature. This refers to the periodical diversion from the normal teaching, and to the emergency distancing in the teaching processes as well. In the present study, we focus on the alteration of student relationships and its correlation with higher educational efficiency, because we see the reduction of student relationships as a discriminatory factor of this period. According to the previous results, the institutional embeddedness of students to be an indispensable condition of educational efficiency. In our study, we compared the states of the student relationships before and after the ERT. We hypothesise that the reduction of institutional relations caused by the epidemic is the cause for the student inefficiency, dissatisfaction, and distrust. Our questionnaire was filled by 677 students (172 males, 505 females) from 30 Hungarian higher education institutes altogether. Our results raise attention to the indispensable roles of instructors which are not in close relation to teaching. Furthermore, the results point that the weakening in the student relationships is in correlation with student persistence, student engagement, and institutional trust and satisfaction. According to the study, the reduction of student embeddedness had a negative impact on performance. A further conclusion is that all of this should be taken into consideration when working out a concept for a virtual university.